Economic security - Defraigne, Jean-Christophe (Palgrave Macmillan, 2021)
This chapter first defines the concept of economic security and goes on to identify the main concerns of the EU and Asia in this domain. It explains why Asia cannot be apprehended as a homogenous block and provides a taxonomy of the Asian economies according to their specificities in order to compare their approach to economic security to the EU’s. In the last part, this chapter looks into the global economic and geopolitical changes that have emerged since 2000 to assess to what extent these changes have generated a convergence or divergence between the EU’s and Asian countries’ perception of economic security. From this, it deduces the scope for potential cooperation between the EU and the different groups of Asian economies.